Synthesis, Characterization, and Energetic Studies of Polynitro Aryl‐1, 2, 3‐2 H‐Triazoles. Issue 1 (26th November 2015) - Kommu, Nagarjuna; Kumar, A. Sudheer; Raveendra, J.; Ghule, Vikas D.; Sahoo, Akhila K.
Abstract: A series of energetic polynitro‐aryl‐1, 2, 3‐2  H ‐triazoles are synthesized from readily accessible aryl‐1, 2, 3‐2  H ‐triazoles. X‐ray diffraction analysis established the solid‐state structures of several representative molecules. The thermal properties are determined by differential scanning calorimetry and thermogravimetric analysis (DSC‐TGA) data. Based on computational studies, most of the compounds showed positive heats of formation and the densities were 1.55 to 1.83 g cm −3 . In addition, the compounds were thermally stable ( T d >210 °C) and exhibited acceptable detonation properties. Abstract : Tri as you might : A series of di‐, tri‐, and tetranitro‐substituted N ‐aryl‐1, 2, 3‐2  H ‐triazole derivatives are synthesized (see figure). The heats of formation of the di‐/trinitro compounds are positive (809.24 and 818.08 kJ mol −1 ), their thermal stability is high (320 and 273 °C), and their detonation velocities are good (8020 and 7840 m s −1 ).